Towers of Semisimple Algebras, Their Graphs and Jones Index - Dlab, Vlastimil (Sarajevo Journal of Mathematics, 2024)
The paper presents an algebraic approach to the theory of pairs of semisimple algebras, the Jones fundamental construction of a tower and its index. The methods of the representation theory of hereditary algebras allows to classify the pairs in terms of a bimodule and a vector space and to describe the values of the Jones index. * This paper was presented at the International Scientific Conference Graded structures in algebra and their applications, dedicated to the memory of Prof. Marc Krasner, IUCDubrovnik, Croatia, September, 22-24, 2016.